2010
DOI: 10.1165/rcmb.2009-0328oc
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relationship between Primary and Motile Ciliogenesis in Airway Epithelial Cells

Abstract: Cilia are traditionally classified as motile or primary. Motile cilia are restricted to specific populations of well-differentiated epithelial cells, including those in the airway, brain ventricles, and oviducts. Primary cilia are nonmotile, solitary structures that are present in many cell types, and often have sensory functions such as in the retina and renal tubules. Primary cilia were also implicated in the regulation of fundamental processes in development. Rare depictions of primary cilia in embryonic ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 46 publications
14
118
0
Order By: Relevance
“…It has been shown that primary cilia are found transiently in the airways but not in well-differentiated airway epithelium. In addition, primary cilia have been observed in the luminal layers of epithelium and basal cells after lung injury (44). Inhibition of notch signaling is known to be involved in the switch from a primary ciliated cell to an MCC (24,27,28,45).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that primary cilia are found transiently in the airways but not in well-differentiated airway epithelium. In addition, primary cilia have been observed in the luminal layers of epithelium and basal cells after lung injury (44). Inhibition of notch signaling is known to be involved in the switch from a primary ciliated cell to an MCC (24,27,28,45).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that air-liquid-interface (ALI) cultures of primary mouse tracheal epithelial cells can be used to evaluate the cellular and molecular mechanisms regulating FBP function (20,29,38,39,(48)(49)(50). We showed that FBP initiate ALI cultures and that K5/K15/K14 triple-positive basal cells comprise 98% of the ALI culture on Culture Day 2 (38).…”
Section: Air-liquid Interface Modelmentioning
confidence: 94%
“…There are two types of cilia: motile and primary cilia (9,10). Airway epithelial cells that are destined to develop motile cilia first generate primary cilia, and therefore the presence of primary cilia represents an early stage of multiciliated cells.…”
Section: Foxa2mentioning
confidence: 99%
“…Airway epithelial cells that are destined to develop motile cilia first generate primary cilia, and therefore the presence of primary cilia represents an early stage of multiciliated cells. Foxj1 expression is not required for primary cilia formation, but is turned on as motile cilia develop (9). The iPSC-derived epithelium described by Firth et al (3) demonstrates acetylated α-tubulin expression on the apical surface of the cells, and is suggestive of primary cilia.…”
Section: Foxa2mentioning
confidence: 99%